The changing characteristics and outcomes of patients undergoing surgical aortic valve replacement in the transcatheter aortic valve implantation era. Issue 4 (April 2015) - Rozen, Guy; Fefer, Paul; Shinfeld, Amichai; Sternik, Leonid; Guetta, Victor; Malachy, Ateret; Levin, Shany; Feinberg, Micha; Raanani, Ehud; Segev, Amit
Abstract : Background: Transcatheter aortic valve implantation (TAVI) is thought to change the characteristics and outcome of patients with aortic stenosis undergoing surgical aortic valve replacement (SAVR). We investigated the difference in clinical characteristics and outcomes of SAVR patients in the TAVI era. Methods: Two cohorts of consecutive patients undergoing isolated SAVR for severe tricuspid aortic stenosis, in 4 years before (period-1) and 4 years after (period-2) the introduction of TAVI were analysed. Primary endpoint of 1-year mortality by Cox proportional hazard models was analysed. Secondary endpoints included 1-year, 30-day mortality and adverse perioperative events. Results: The study consisted of 207 patients in period-1 and 200 in period-2. Mean age was 74.9 ± 9.6 and 73.5 ± 9.4 years in periods 1 and 2, respectively. Mean EuroSCORE was 11.5 ± 10.3 during period-1 vs. 8.4 ± 7.2 during period-2 ( P  = 0.001). One-year mortality decreased from 15.5 to 7.5% ( P  = 0.013). Composite of major adverse perioperative complications dropped from 12.6 to 6% ( P  = 0.027). EuroSCORE was an independent predictor of 30-day and 1-year mortality in period-1 ( P  < 0.005 for both) and not in period-2. Chronic pulmonary disease and preoperative atrial fibrillation were also independent predictors of 1-year mortality in period-1 only, although lower haemoglobin predicted mortality in both periods. Conclusion: We show a dramatic decrease in 1-year mortality and adverse perioperative events in patients undergoing SAVR for severe aortic stenosis during recent years. This change is likely related to selection of lower-risk patients for AVR in the TAVI era.